Healable, Transparent, Room‐Temperature Electronic Sensors Based on Carbon Nanotube Network‐Coated Polyelectrolyte Multilayers. Issue 43 (23rd September 2015) - Bai, Shouli; Sun, Chaozheng; Yan, Hong; Sun, Xiaoming; Zhang, Han; Luo, Liang; Lei, Xiaodong; Wan, Pengbo; Chen, Xiaodong
Abstract : Transparent and conductive film based electronics have attracted substantial research interest in various wearable and integrated display devices in recent years. The breakdown of transparent electronics prompts the development of transparent electronics integrated with healability. A healable transparent chemical gas sensor device is assembled from layer‐by‐layer‐assembled transparent healable polyelectrolyte multilayer films by developing effective methods to cast transparent carbon nanotube (CNT) networks on healable substrates. The healable CNT network‐containing film with transparency and superior network structures on self‐healing substrate is obtained by the lateral movement of the underlying self‐healing layer to bring the separated areas of the CNT layer back into contact. The as‐prepared healable transparent film is assembled into healable transparent chemical gas sensor device for flexible, healable gas sensing at room temperature, due to the 1D confined network structure, relatively high carrier mobility, and large surface‐to‐volume ratio. The healable transparent chemical gas sensor demonstrates excellent sensing performance, robust healability, reliable flexibility, and good transparency, providing promising opportunities for developing flexible, healable transparent optoelectronic devices with the reduced raw material consumption, decreased maintenance costs, improved lifetime, and robust functional reliability. Abstract : A healable and transparent chemical gas sensor is assembled from carbon nanotube network (CNT)‐coated polyelectrolyte multilayers. The layer‐by‐layer assembled polyelectrolyte multilayers successfully impart healability to the CNT network layer by the lateral movement of the underlying self‐healing layer, which brings the separated areas back into contact. It exhibits robust flexibility, good transparency, and reliable healability of the sensing performance.